Beyond troubled and untroubled positions – an intersectional analysis of siblings who are bereaved by drug-related deaths’ meaning-making stories about their deceased brothers and sisters - Gunhild Meen; Monika Alvestad Reime; Sari Lindeman; Lillian Bruland Selseng (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study investigates how social categories work and intersect in siblings bereaved by drug-related deaths’ (DRDs) stories about their relationships to their deceased brother or sister. The sociocultural embedded process of making meaning of the relationship with the deceased individual is essential in adapting to the loss. However, insight into such experiences of siblings bereaved by a DRD is scarce. Previous research has suggested that DRDs may be stigmatized life experiences for bereaved family members, and this paper furthers understanding of the experiences and issues involved in losing a sibling in a stigmatized death. Methods An intersectional analysis is applied to interviews with 14 bereaved siblings. By investigating and displaying how different categories intertwine, various positionings are identified. Findings Categorization of the deceased siblings as “addicts” constructs a troubled position. However, when “addict” intersects with the categories “unique,” “sibling,” and “uncle,” the troubled subject’s position as an “addict” can be concealed. Conclusions Normative conceptions of addiction and DRDs produce troubled subject positions. By intermingling the category of “addict” with other categories, less problematic positions are created. Still, intersections of categories can also construct further complexities of remorse and self-blame for the bereaved siblings.